Development of spatial similarity-based modeling to support integrated lake water quality management: recreational lakes in Klang Valley, Malaysia - Fazli, Bashirah; Shafie, Aziz; Mohamad, Mohd Fauzi (University of Akron, 2018)
Due to recent climate factors which lead to long dry spells and affect normal water distribution from the reservoir, there is a high potential for tapping water from recreational lakes as a resource alternative for high population density states in Malaysia such as Selangor and Kuala Lumpur. The challenges, however, are due to severe data limitations, no formation of a regular water quality monitoring programme and segregated catchment planning. This paper intends to discuss the application of similarity- based modeling as the alternative technique for integrated lake water quality management under the circumstances of severe data limitation issues and a limited programme of continuous lake water quality sampling and monitoring. The developed spatial model applies a similarity-based technique, with a distance of 1km buffer radius set as model database. LakePutrajaya has been chosen as similarity assessment control point due to its comprehensive data availability and long-term monitoring. Findings showed that a similarity technique of spatial modeling is acceptable to be applied as a preliminary assessment tool for a lake with limited data. Based on the 93 recreational lakes in the study area, none came under the category of either bad or excellent. The majority are in class three of medium water quality status, with only four lakes considered as having a good condition of water quality and the remainder of thirty-five lakes are considered to have poor water quality. Validation analysis of the developed model indicates that the model function is satisfactory as a preliminary decision support tool for recreational lake managers with limited data and no established monitoring programmes.